Search Space Reduction Using Swamp Hierarchies - Pochter, Nir; Zohar, Aviv; Rosenschein, Jeffrey; Felner, Ariel (Proceedings of the International Symposium on Combinatorial Search, 2010)
In various domains, such as computer games, robotics, and transportation networks, shortest paths may need to be found quickly. Search time can be significantly reduced if it is known which parts of the graph include "swamps" - areas that cannot lie on the only available shortest path, and can thus safely be pruned during search. We introduce an algorithm for detecting hierarchies of swamps, and exploiting them. Experiments support our claims of improved efficiency, showing significant reduction in search time.